Removal of phenolic compounds from aqueous solutions by fungal biosorbent - Phon, Chee Wah (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
The highly toxic nature of phenolic compounds is a worldwide environmental problem. Objective of this project is to investigate the removal of phenolic compounds from aqueous solution by fungal biosorbent. The phenolic compounds used in this project were 2-chlorophenol and 2, 3-dichlorophenol. The fungal biosorbent which is Aspergillus terreus UniMAP AA-1 was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) techniques. The effects of physicochemical parameters studies such as initial phenolic compounds concentration, pH and biosorbent dosage amount were evaluated. The adsorption isotherms data were analyzed using Langmuir and Freundlich isotherms models. The results showed that the correlation coefficient, R2 of Freundlich isotherm is higher than that of Langmuir Isotherm. For the kinetics study, pseudo-first order and pseudo-second order were used to examine the experimental data at different initial concentration. Pseudo-second order has highly correlative coefficient, R2 > 0.99 and the calculated qe values fit well for the biosorption of phenolic compounds on the Aspergillus terreus fungus. Aspergillus terreus fungus appears to be a promising biosorbent material for removal of phenolic compounds from aqueous solution due to their high adsorption capacity, high kinetic rates and low cost of process.